Oviposition preference and larval performance of Epiphyas postvittana (Lepidoptera: Tortricidae) on Botrytis cinerea (Helotiales: Sclerotiniaceae) infected berries of Vitis vinifera (Vitales: Vitaceae). (31st March 2015) - Rizvi, Syed Z. M.; Raman, Anantanarayanan; Wheatley, Warwick M.; Cook, Geoffrey
Abstract: In this paper we tested the behavior of gravid Epiphyas postvittana in selecting the most‐appropriate site for oviposition thus benefitting offspring performance. Our hypothesis was built on Jaenike's preference–performance hypothesis (also referred to as the "mother‐knows‐the‐best" hypothesis). To test this, we used the interacting Epiphyas postvittana, its host Vitis vinifera, and the pathogenic microbe Botrytis cinerea system. Populations of E. postvittana and B. cinerea often exist concurrently on V. vinifera in Australasia and their interaction and mutual influence are currently being explored, although the suggestion presently is that the relationship between E. postvittana and B. cinerea is mutualistic. We tested the effect of volatiles from B. cinerea ‐infected berries and uninfected (control) berries of V. vinifera on the oviposition behavior of E. postvittana . We also characterized the effects of B. cinerea infection on the berries of V. vinifera on the growth and development of E. postvittana . Contrary to the preference–performance hypothesis, oviposition choices made by gravid E. postvittana did not result in the best offspring survival, development, and performance. The preference for oviposition by E. postvittana was strongly influenced by the olfactory and tactile cues. She laid fewer eggs on B. cinerea ‐infected berries compared to uninfected berries of V. vinifera . The larvae of E. postvittana showed no preference to uninfected berries of V. vinifera . The larvae fed on B. cinerea ‐infected berries of V. vinifera showing greater survival rate, shorter time to pupation, greater pupal mass, and on becoming adults they laid more numbers of eggs than the larvae that were enabled to feed on uninfected berries. The larvae of E. postvittana transport the conidia of B. cinerea and transmit grey‐mould disease to uninfected berries of V. vinifera .